Educational Policies of Writing and Reading (A commentary on D.G. Ryndin’s article “Merab Mamardashvili: event of thought and pedagogic practice”) - A. A. Polonnikov (Высшее образование в России)
The paper contains an “asymmetric commentary” on a philosophical text by means of its subsequent placing in the educational contexts. The first of them is related to an explication of the cultural mission of a pedagogical project suggested by the article. The second one is aimed at the analysis of the pedagogical action of the text determined by the writing/reading samples placed in it. The third one performs the function of a counter-text problematizing a pedagogical program of the article being commented. The exhaustion of orientation to symbolic identification with invariant symbols of culture is substantiated. Educational transformation is connected with overcoming the methodological individualism. Education is transformed into a subject of public collaboration. The emphasis in collective work has to be placed not on establishment of the coordinated definition situation, but on the conflict of its interpretations, collision of practical positions and detection of qualitatively various educational prospects. The commentary by means of the trial-and-error method also researches a possibility of building a demonstrative description able to cause dereification effects in the writing/reading processes. It is supposed that deconstructive writing can become a major element of students’ academic competence in the process of university training.